Fitness of Japanese encephalitis virus to Neuro-2a cells is determined by interactions of the viral envelope protein with highly sulfated glycosaminoglycans on the cell surface - Chiou, Shyan-Song; Liu, Hsuan; Chuang, Ching-Kai; Lin, Chiou-Chun; Chen, Wei-June (Journal of medical virology, 2005)
Genetically different subpopulations were identified and purified from Japanese Encephalitis virus (JEV). Those with small plaques (SPs; <2 mm in diameter), derived from strains of T1P1, CJN, and CC27, were more competent than those with large plaques (LPs; >5 mm in diameter) when passaged in Neuro‐2a cells. Differences in amino acids between SPs and LPs from each strain were shown in the viral envelope (E) protein. The amino acid at E‐306 was Glu in LP but was substituted by Lys in SP in the T1P1 strain. A similar substitution occurred at E‐138 in the CJN strain. However, the amino acid was Asp in LP but was substituted by Asn in SP at E‐389 in the CC27 strain. All SPs were shown to have a higher affinity to the cellular membrane when compared to LPs, and this resulted in more‐efficient infection of Neuro‐2a cells, suggesting that the differential fitness of JEV variants to Neuro‐2a cells appeared in the early phase of infection. In addition, glycosaminoglycans (GAGs) on the surface of many mammalian cells have been demonstrated to be critical for infection by JEV, especially SP variants. The present results suggest that T1P1‐SP1 viruses infected Neuro‐2a cells more efficiently in spite of the sparse distribution of cell surface GAGs. We conclude that highly sulfated forms of GAGs expressed by Neuro‐2a cells play an important role in selecting JEV variants with specific mutations in the E glycoprotein. J. Med. Virol. 76:583–592, 2005. © 2005 Wiley‐Liss, Inc.